Sistem Pendukung Keputusan Seleksi Penentuan Penerima Beasiswa Dengan Metode Simple Additive Weighting (SAW) - Handoko, Donny; , Fatah Yasin Irsyadi, S.T., M.T (2016)
Educational institutions especially universities lots of scholarships offered to students. The awarding of scholarships are also given to students in the Faculty of communication and Informatics, namely in the form of scholarships PPA and BBM. Some of the problems that often occur e.g. the selection process is not accurate because of the large number of applicants scholarship that should be adapted to the existing criteria, then in turning students who get not even entitled to scholarships and students who do not qualify for a scholarship instead of getting scholarships and the selection process is still a manual because student data will be compared individually with the scholarship criteria so that the process selection needs a thoroughness and time then this is not efficient. Decision support system applications is a way to address the issue of the determination of the scholarship recipients. This app uses Fuzzy Multiple Attribute Decision Making (FMADM) by the method of Simple Additive Weighting (SAW). SAW method was chosen because this method determines the weighting of each criterion specified later in the process of normaliasi in accordance with the existing equations method SAW and continued with the process of rank for selecting the best alternative, in this case the question is students are eligible to receive a scholarship. The results of this research in the form of the application of decision support system of selection determination of scholarship recipients with simple additive weighting method is web-based. Based on the results of the research of the application of decision support system of selection determination of scholarship recipients by the method of simple additive weighting (SAW) it facilitates the selection part of Student Affairs Bureau scholarship awardees for the determination of appropriate criteria, the more quickly and right on target as expected.